The relationship between students perception and students interests at sman 2 takalar in continuing nursing studies - Suardi, Suardi (CV. Paperhome Indonesia, 2025)
Background: Perception which is the result of this cognitive ability process will provide encouragement to individuals so that motivation emerges which will direct a person's behavior to act. Objective: To determine the relationship between student perceptions and SMAN 2 Takalar students' interest in continuing their nursing studies. Method: This research is descriptive and analytical with a cross sectional design. With a population of 238 students and a sample of 238 respondents, data processing/testing of the Fisher's Exact Test is presented in the form of narratives and tables. Results: This research shows that there is no relationship between student perceptions and interest. There is a relationship between student perceptions and SMAN 2 Takalar students' interest in continuing their nursing studies. The Fisher Exact Test obtained a Continuity Correction value (P=0.574). Conclusion: in this study there is no relationship between student perceptions and SMAN 2 Takalar students' interest in continuing their nursing studies